Major constraints and trends for common bean production and commercialization; establishing priorities for future research - Rodríguez De Luque, Jesús José; Creamer, Bernardo (Universidad Nacional de Colombia, 2014)
In order to identify the principal constraints and trends for common bean production and commercialization and the priorities for future common bean research in Africa, Latin America and the Caribbean (LAC), a priority setting process was developed at the International Center for Tropical Agriculture (CIAT). The results suggested that the principal research included breeding and selecting for several traits, such as drought tolerance and water use efficiency, improved yields, and consumer acceptance (improved cooking time and desired texture after cooking). Additionally, the results of the priority setting process suggested that institutional measures are needed, such as improving formal seed production and distribution channels and the development of national and regional seed policies. On the other hand, the identified principal constraints included diseases, pests, and market constraints. Finally, the identified principal trends were: increase in demand and production, and development of high-yield varieties and improvement in nutritional quality.